Correlates of brain-stem oculomotor disorders in multiple sclerosis. Magnetic resonance imaging. - Bogousslavsky, J; Fox, A; Carey, L; Vinitski, S; Bass, B; Noseworthy, J; Ebers, G; Barnett, H (1986)
Three patients with focal brain-stem oculomotor disturbances (nuclear sixth nerve syndrome, sixth nerve palsy, bilateral internuclear ophthalmoplegia) as a consequence of multiple sclerosis have been studied with high-volume delayed computed tomography and high-field magnetic resonance imaging. In all of them, high-volume delayed computed tomography was inconclusive in the brain stem, but magnetic resonance imaging showed an area of prolonged T1 and/or T2 in the region appropriate to the oculomotor findings. Magnetic resonance imaging is the imaging technique of choice of small plaques in the brain stem. It can considerably aid clinicotopographic correlation in multiple sclerosis.